Transcriptional Riboswitches Integrate Timescales for Bacterial Gene Expression Control - Scull, Catherine E.; Dandpat, Shiba S.; Romero, Rosa A.; Walter, Nils G. (Frontiers in Molecular Biosciences, 2021)
Transcriptional riboswitches involve RNA aptamers that are typically found in the 5’ untranslated regions (UTRs) of bacterial mRNAs and form alternative secondary structures upon binding to cognate ligands. Alteration of the riboswitch’s secondary structure results in perturbations of an adjacent expression platform that controls transcription elongation and termination, thus turning downstream gene expression “on” or “off”. Riboswitch ligands are typically small metabolites, divalent cations, anions, signaling molecules, or other RNAs, and can be part of larger signaling cascades. The interconnectedness of ligand binding, RNA folding, RNA transcription, and gene expression empowers riboswitches to integrate cellular processes and environmental conditions across multiple timescales. For a successful response to an environmental cue that may determine a bacterium’s chance of survival, a coordinated coupling of timescales from microseconds to minutes must be achieved. This review focuses on recent advances in our understanding of how riboswitches affect such critical gene expression control across time.